Redesign Tata Letak Produk Berdasarkan Perilaku Pembelian Konsumen Menggunakan Metode Algoritma Apriori - Cindi Wulandari; Rusdiyanto; M Rama Barokah Setian Jaya (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The development of technology has had a huge impact on human life. One of these influences in the field of information is the use of computers as a useful medium for companies by trying to collect as much information as possible to get maximum profit. In addition, the use of database systems plays a very important role for data management and is needed in various aspects of life, both in education, business, banking, and others. Mars Mart stores currently sell baby supplies, which provide a variety of products. The pandemic period has greatly affected the sales process at Mars Mart Store. So that shop owners must be good at organizing merchandise so that it is easy to see and attract the attention of buyers. The effect of the pandemic is that the raw materials take a long time to sell so that within 1 year the goods that should have been sold become unsold and expired. It is hoped that the system for determining the layout of merchandise can help sellers to increase sales of these goods because the display of merchandise is in accordance with consumer purchasing patterns. The method used to solve existing problems is the Apriori algorithm has two main processes, namely merging (join) and pruning (prune). The join process is a process that combines each existing item with other items until no more combinations can be formed, and the result of this research is that there are 6 rule bases that exist